Towards a green public bank in the public interest - Thomas Marois (United Nations Research Institute for Social Development (UNRISD), 2018)
Four decades of neoliberal market fundamentalism and its relentless assault on the public sector and our understandings of publicness have generated a profound crisis of social reproduction and environmental sustainability. Private sector financial solutions and market signals have not tackled climate change at the speed and magnitude required, often instead magnifying our social, economic, political, and environmental challenges. This paper discusses the rediscovery of public banks and their potential - to finance low-carbon, climate-resilient development, and as a public sector alternative that can overcome the shortcomings of the private sector and market approaches mentioned above. The paper suggests an ideal-type public bank that would be needed for a green transformation that is also in the public interest. The ideal type is crafted around five central features: mandated role; financial sustainability; operational strategy; democratization of governance; and integral integration of workplace and community. The defining characteristics of each feature can be found in existing public banks. Putting forward an alternative conceptualization that focuses on the public interest, sustainability and social equity concerns, this paper contributes important insights to the current debates on sustainable development and a just and equitable green transformation.
Additional information: Paper prepared for the UNRISD session at the Resilience 2017 Conference
Keywords: 330